Fluoroscopy Dose and Time During Vertebral Augmentation for Spine Pain Due to Malignant Fractures - Carlos J. Roldan; Thomas Chai; Lei Feng; Ian Huh; Billy Huh (Radiation)
Background: Vertebral augmentation (VA) procedures are used to treat painful vertebral fractures caused by malignancies, but there are few data on the radiation exposure for patients and proceduralists during these VA procedures. We retrospectively examined the radiation dose exposure during VA procedures and defined the characteristics of patients who underwent such procedures. Methods: We conducted a retrospective observational cohort study including patients with cancer who experienced axial back pain from compression fractures caused by malignancies. Participants were identified using an electronic medical records database and must have had evidence of stable vertebral compression fractures upon imaging and documentation of a clinical evaluation. We collected data on patient demographics, fluoroscopy time (FT) and dose (FD) during the procedure, the volume of polymethylmethacrylate injected, and reported complications. Results: Overall, 140 patients were included. Their median age was 69, and they were mostly men (n = 79). The most common diagnosis was multiple myeloma (41.4%). Most patients had a single-level compression fracture of the thoracolumbar spine. The mean FT was 233.80 s, with higher FTs for patients with an elevated body mass index and patients younger than 60 years. The average FD was 157.98 mGy, with higher FDs for patients with an elevated BMI and for male patients. Pain relief was not associated with FT or FD. Conclusions: Patients with cancer who underwent VA experienced longer FT and higher FD compared to their non-cancer counterparts in the literature. However, we found multiple confounders for this relationship.